EXPERIENCE OF ORGANIZING OF THE RADIATION SITUATION MONITORING, DEVELOPMENT AND IMPLEMENTATION OF MEASURES TO MINIMIZE RISKS OF RADIATION EXPOSURE OF THE MAGADAN REGION POPULATION RELATED TO THE FUKUSHIMA ACCIDENT BY THE ADMINISTRATION OF THE FEDERAL SERVICE FOR SURVEILLANCE ON CONSUMER RIGHTS PROTECTION AND HUMAN WELL-BEING IN MAGADAN REGION AND FEDERAL HEALTH ORGANIZATION "CENTER OF HYGIENE AND EPIDEMIOLOGY IN MAGADAN REGION" - A. A. Rubtsova; P. N. Chebotarev; K. A. Grachev; T. Yu. Parfenova (Радиационная гигиена)
The article presents results of activities of the Administration of the Federal Service for Surveillance on Consumer Rights Protection and Human Well-being in Magadan region and the Federal Health Organization "Center of Hygiene and Epidemiology in Magadan region" in the context of monitoring of the radiation situation in the Magadan region from 12.03.2011 in connection with the Fukushima accident in Japan. The authors present the data on radiological laboratory studies, the analysis of performed organizational activities, the results of co-operation with the state and other regulatory authorities.